Avaliação em laboratório do efeito da formulação e das propriedades de graxas lubrificantes no desempenho tribológico do contato roda-trilho - Ferrer, Bruno Pereira (2020)
Tribological phenomena in the wheel-rail interface are complex. In sharp curves, the severe contact conditions lead to high values of friction and wear. Excessive friction increases fuel consumption (highest material cost on railways) and wear is a predominant factor for replacing rails and wheels (second and third highest material costs on railways). In order to reduce friction and wear, there is grease lubrication in the gauge rail, which is in contact with the wheel flange, mostly in the curved regions. Due to the variety of non-controllable parameters, the time to obtain results and the safety of operation, field tests do not allow evaluating many options of lubricating greases. In this sense, this project presents two laboratory tests as alternatives: pin-ondisc, to evaluate the performance of sliding grease, and grease flow in an open environment, as one of the grease performance factors in retentivity. The methodology consisted of optimizing the tribosystem (type of contact, material, topography, load, speed, temperature and time) só that the wear regime and the conditions observed in the field, on the Vitória-Minas Railway Road, and obtained from the literature were reproduced. In total, eleven greases were evaluated, five of them commercial and six of internal formulation, generating results that allowed correlations between performance and grease properties. The main conclusions are: i) lithium greases showed less friction and wear, ii) the higher the kinematic viscosity, the less wear and more the friction is independent of the thickener type and iii) the critical speed to expel the grease is related to two factors, yeld shear stress of the grease and adhesion on the surface of the material, this last topic not investigated at this project.